Assessment on dietary exposure of aluminum among adult residents in Qinghai Province - ZHANG Qian; GUO Xuebin (Zhongguo shipin weisheng zazhi, 2021)
ObjectiveTo evaluate the dietary exposure level of aluminum and its potential health risk among adult residents in Qinghai Province.MethodsIn this paper, the aluminum content of 499 samples of 7 kinds of main aluminum containing foods in Qinghai Province from 2015 to 2020, the Fifth China total dietary study and the food consumption data of nutrition and health monitoring of Chinese residents from 2010 to 2013 were used. The exposure level and potential risk of dietary aluminum in different age and sex groups of residents in Qinghai Province were evaluated by point evaluation method .ResultsThe average content of aluminum in 7 kinds of main aluminum containing foods was 72.210 mg/kg, and the maximum was 1 220.000 mg/kg. The total detection rate was 77.96% (389/499), and the total over standard rate was 19.72% (57/289), among which the detection rate and over standard rate of instant jellyfish were 100.00% (11/11) and 90.91% (10/11) respectively. The average daily exposure of aluminum was 0.080 mg/(kg·d), accounting for 27.86% of the weekly provisional tolerable intake (PTWI). The contribution rate of cereals and their products was the highest, reaching 88.07%. Among the adult residents of different age and gender groups, the daily aluminum exposure of women aged 60 and above was the highest, with an average of 0.086 mg/(kg·d), accounting for 30.05% of PTWI. The median and average dietary aluminum exposure were both less than 1 of the PTWI.ConclusionThe health risk of dietary intake of aluminum among adult residents in Qinghai Province was low, and cereals and their products were the main contribution foods.